The Role of Positive Reinforcement on Students in English Language Learning: A Skinnerian behaviorist: English - Tia Kurnia Sari; Putri Hanifah Rahmani (JOEY: Journal of English Ibrahimy, 2024)
Operant conditioning, also known as instrumental conditioning, involves the use of rewards and punishments to establish a relationship between behavior and its consequences, both positive and negative. Positive reinforcement involves introducing desired stimuli, while negative reinforcement involves removing unwanted stimuli. Both positive and negative reinforcement aim to strengthen The exhibited behavior. This research aims to explore the role of positive reinforcement in motivating students in English language learning. The data for this study were obtained through interviews with English teachers in schools in Surakarta who have been teaching English for a minimum of 3 years. The data were then analyzed using qualitative descriptive methods. The results of the interviews indicate that the use of positive reinforcement in the classroom is highly beneficial for motivating students to learn English. A safe and comfortable classroom environment is also essential to support learning activities.